Development of the Personnel Risks Assessment and Supply Chain Strategy as a Basis of the Risk Management System of Modern Organizations - Tatyana V. Tselyutina; Olga A. Timokhina; Tatyana A. Vlasova; Yana V. Maslova (International Journal of Supply Chain Management, 2019)
The integration of risk management technologies into the business processes of modern organizations serves as the key to highly efficient, stable and sustainable development of any business entity by considering the supply chain strategy. The sphere of management of personnel flows of organizations calls for special attention and needs an adaptive, flexible and integrated risk management system able to ensure both the timely achievement of strategic goals and a high level of personnel security of organizations. The objective of the study is to analyze existing personnel risks and develop an adaptive, universal methodology for assessing their likelihood, with further modeling of possible risk scenarios. In the framework of the study, a two-stage method for estimating the probability of occurrence of 30 personnel risks characteristic of different types of personnel flows was tested. Possible scenarios were simulated using the Scenario Manager method. Modern Russian trade organizations seeking to build an effective personnel security management system can use the methodical approach proposed by the authors in their risk management system.